Protective effects of spironolactone against hepatic ischemia/reperfusion injury in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; ERZİK, CAN; ÖZKAN YENAL, NAZİYE; ÇETİNEL, ŞULE (TURKISH SURGICAL ASSOC, 2019)
Objective: In the present study, it was aimed to study the antioxidant effects of spironolactone (SPL) to determine its possible protective effects in hepatic ischemia reperfusion injury. Material and Methods: Hepatic artery, portal vein, and bile duct of Wistar albino rats were clamped for 45 minutes under anesthesia to form an ischemia period. Then reperfusion was allowed and the rats were decapitated 60 minutes later. SPL (20 mg/kg, p.o.) or SF was orally administered for 30 minutes before ischemia. Rats in the control arm underwent sham surgery and were administered isotonic saline. Liver function was studied by measuring aspartate aminotransferase (AST), alanine aminotransferase (ALT), tumor necrosis factor-alpha (TNF-alpha), and interleukin 1beta (IL-1 beta) levels. Malondialdehyde (MDA), glutathione (GSH), luminol, and lucigenin levels, myeloperoxidase (MPO) and Na+-K+- ATPase enzyme activities were analyzed to study tissue injury under light microscope. Results: While IR increased AST, ALT, TNF-alpha, and IL-1 beta levels and MDA, luminol, and lusigenin levels and MPO activities, it caused a decrease in GSH levels and Na+K+-ATPase activity. Spironolactone administration significantly improved these values. Conclusion: Protective effects of SPL against ischemia/reperfusion injury via various mechanisms suggest that this agent may become a novel treatment agent in clinical practice.
Keywords: Hepatic ischemia reperfusion; spironolactone; malondialdehyde; glutathione; cytokines; ISCHEMIA-REPERFUSION INJURY; MELATONIN PROTECTS; LIVER-INJURY; RECEPTORS; APOPTOSIS